The Impact of Reading Strategy Instruction Based on QAR with Visually-Oriented Learners - Annury, Muhammad Nafi; Sutrisno, Djoko; Mariam, Siti; Kepirianto, Catur (Master Program in Linguistics, Diponegoro University, 2023)
Language learning styles and strategies have been developing for several years as one of the crucial parts of language learning. Metacognitive techniques have been looked into as aids for improving pupils' reading comprehension. The metacognitive strategy instruction should be integrated with students' different learning styles to help them be more effective and autonomous learners. Even though learning styles are crucial to language acquisition, few studies have examined the relationship between perceptual language learning and Indonesian students' use of metacognitive reading strategies. This study examined how metacognitive techniques were used when academic reading from a visually oriented standpoint to fill the gap. An open-ended questionnaire was employed in a descriptive quantitative study. There were fifteen experimental and fifteen students in the experimental class, and the data were analyzed quantitatively. They used a reading comprehension test adopted from the Baron TOEFL reading section to achieve the pre-test and the post-test scores. The statistical results showed a significant interaction in metacognitive strategy with a visually oriented style in pre and post-test with a p-value of 0.000 (p<0.05). The results of this study will persuade English teachers to provide metacognitive reading methods through suitable instructions and supervision so that students may put them into practice and advance their reading comprehension.